Can HF heating generate ESF bubbles?. Issue 23 (2nd December 2014) - Zawdie, K. A.; Huba, J. D.
Abstract: The injection of powerful HF waves into the ionosphere can lead to strong electron heating followed by a pressure perturbation which can locally reduce the plasma density. In the postsunset equatorial ionosphere, density perturbations can provide the seed to generate equatorial spread F (ESF) bubbles. In this paper, a modified version of the SAMI3/ESF ionosphere code is used to model the density depletions created by HF heating and to determine if ESF bubbles can be artificially generated. It is found that HF heating primarily redistributes plasma along the geomagnetic field and does not significantly perturb the flux tube integrated conductivities. Thus, HF heating does not appear to be a viable method to seed or generate ESF bubbles. Key Points: HF heating does not appear to be a viable method to generate ESF bubbles HF heating likely cannot suppress ESF bubbles HF heating does not deplete electron density along the entire field line